unpublished texts from Picasi city in Tal abu Anteak - Mohammed, Ahmed Kamil; Habeeb, Shaymaa Abdel zahra (Al-Adab Journal, 2018)
Tel Abu Antiq is located in an area that has borders with three governorates, which are Bebel from Altaleea Side, Alnajaf Alashraf nearby Alhurriya sub district and Alqadisiya Al mhannawiya sub district. It is around 50 km away to the south of the historic city of Babel. It is located western to the archeological city of Mard 15km away nearly. . The location is famous of agriculture like the date palms and rice in particular. The hill is penetrated by drainage 20m wide known as Al haffar or the Eastern Drainage. The Drainage located to the west of it is called Alqawsi. It was dug to dry up the marshes waters in 1994. The highest point in the hill reaches 20m above sea level. The lands surrounding the hill were plain, fertile and suitable for agriculture. Many decades ago the lands were immersed by waters of Ibn Najim Marsh; one of Alshamiya and Almishkhab marshes. This immersion led to disapearance of its features. It was forgotten by the Archeological inspectors who surveyed the agricultural lands within the farms especially those were subject to settlement of the land rights in the thirties of the last century. The state organization for archeology and heritage marked in their records and maps at that time two archeological hills connected by an old irrigation canal, they are at close distance from Abu Antiq hill. The 1st is known as (Zghaitan), it is to the south west of Abu Antiq. The second is known as (Jeghaiman) to the North West. Total area of both hills with Abu Antiq is 9 square kilometers. They all make mostly a settlement. The surface areas of Zghaitan hill indicates that it belongs to the aancient babylonic era.